HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS VIII SMPN 1 KARANG PENANG SAMPANG - Faizah, Nurul; Hadi, Wiwin Puspita; Tamam, Badrud; Qomaria, Nur; Yasir, Mochammad (Natural Science Education Research, 2023)
This study aims to determine the feasibility and student responses to the relationship between learning motivation and student learning outcomes in grade VII SMPN 1 Karang Penang Sampang. This research is an ex-post facto research with a quantitative approach. The subjects of this study were all students of class VIII SMPN 1 Karang Penang with a total of 31 students. The results of this study indicate that there is a relationship between students' learning motivation and student learning outcomes in Natural Science subjects in the even semester of the 2021/2022 academic year with a significance value of 0.002 less than 0.05 and a calculated F of 0.535% with a fairly valid category. know that there is a relationship between motivation and student learning outcomes.